An analytical method to estimate the total installed cost of structural steel building frames during early design. (January 2018) - Barg, Steve; Flager, Forest; Fischer, Martin
Abstract: This paper presents a new method to quickly and accurately estimate the material, fabrication, and erection cost of steel frames based on early-design information. To use the proposed Integrated Steel Design (ISD) method, engineers first upload a structural model consisting of a frame layout with preliminary member sizes and connection types specified. The frame connections are then automatically detailed to produce a bill of quantities suitable for fabrication. Next, the total installed cost is estimated based on unit rates maintained by suppliers on a secure web portal. Finally, the cost feedback is provided in the context of the 3-D model in near real-time. We apply the proposed analytical method to several moment frames to illustrate its advantages compared to more approximate approaches. These initial results demonstrate the potential of the ISD method to improve early stage design decision-making through better vertical integration of project information in the AEC industry. Abstract : Highlights: Analytical cost estimate based on early-design information. Automated connection detailing of steel frame structures. Web portal allows steel suppliers to maintain current cost data. Cost data visualization in the context of the building information model (BIM). Demonstration of the benefits of vertical integration in the AEC industry.